A Framework for the Comparative Study of Language. (1st July 2013) - Uriagereka, Juan; Reggia, James A.
Comparative studies of language are difficult because few language precursors are recognized. In this paper we propose a framework for designing experiments that test for structural and semantic patterns indicative of simple or complex grammars as originally described by Chomsky. We argue that a key issue is whether animals can recognize full recursion, which is the hallmark of context-free grammar. We discuss limitations of recent experiments that have attempted to address this issue, and point out that experiments aimed at detecting patterns that follow a Fibonacci series have advantages over other artificial context-free grammars. We also argue that experiments using complex sequences of behaviors could, in principle, provide evidence for fully recursive thought. Some of these ideas could also be approached using artificial life simulations, which have the potential to reveal the types of evolutionary transitions that could occur over time. Because the framework we propose has specific memory and computational requirements, future experiments could target candidate genes with the goal of revealing the genetic underpinnings of complex cognition.